USE OF ONTOLOGY IN INFORMATION SYSTEM TO ASSIST IN THE FORMATION OF AN INDIVIDUAL EDUCATIONAL TRAJECTORY OF STUDENTS - DUBAS, Yurii; KUNANETS, Nataliia (Herald of Khmelnytskyi National University. Technical sciences, 2023)
This work examines the problem of individual educational trajectory in Ukraine. During research, it was found that this issue is considered mainly from a theoretical aspect, which results in the lack of effective and convenient tools for practical implementations to solve the problem. The analysis of existing methods and means of solving the problem has been carried out. The results of the analysis indicate that the implemented information systems partially satisfy the needs of students in the formation of an individual trajectory.Objective. Develop an information system model to help in the formation of an individual educational trajectory for students of higher educational institutions, taking into account the needs of leading IT companies and students' inclinations. Aiding students in the formation of an IET is based on a set of recommendations formed based on student preferences.Method. To solve the problem information system model was developed, which uses two main modules to operate. First module allows its user to pass a career guidance test and second module provide the semantic algorithm to determine disciplines best suited for user based on his professional inclinations. Levenstein's algorithm using ontology was chosen as a semantic algorithm.Results. During research information system was developed which allows students to receive recommendation for formation of individual educational trajectory. Conducted experiments with random input data had shown the system is fully functional and performing its task. All operational aspects of the system are presented in this work using UML diagrams.Conclusions. Forming recommendations for an individual educational trajectory is a complex process that requires a significant amount of resources. The use of information technologies allows to simplify this process, and the development of an information system - to automate it and make it accessible. The implementation of the information system model made it possible to understand all the subtleties of the process of forming recommendations and ensure their accuracy. The operation of the information system was ensured by the use of two modules to determine the user's professional orientation and search for the appropriate discipline. The process of finding a discipline that will match the professional inclination of the user is based on work with semantics, for which the ontology was used. The use of ontology in the process of determining semantic proximity using the Levenshtein algorithm made it possible to obtain semantic units that are as close as possible to the student's professional inclinations and ensure the most accurate result when formulating recommendations.
Keywords: individual educational trajectory; information system; ontology; levenshtein distance